The pregnancy outcomes of infertile women with polycystic ovary syndrome undergoing intrauterine insemination with different attempts of previous ovulation induction - Gao, Yining; Jiang, Shutian; Chen, Li; Xi, Qianwen; Li, Wenzhi; Zhang, Shaozhen; Kuang, Yanping (Frontiers in Endocrinology, 2022)
Background: Polycystic ovary syndrome (PCOS) is one of the most common reasons for infertility. The consensus of the treatment of infertile women with PCOS is ovulation induction (OI) for 6-9 attempts before in-vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI). Nowadays, more attention was paid to a rising, noninvasive treatment, intrauterine insemination (IUI), as some experts claimed IUI could benefit PCOS patients with infertility. Our study means to investigate the outcomes of IUI for PCOS patients and if patients’ previous OI cycles can be a predictive factor for IUI outcomes. Methods: A total of 1086 PCOS patients was included and 1868 IUI cycles were performed between January 2007 and July 2021 in the department of assisted reproduction in Shanghai ninth people’s hospital. All included patients underwent IUI treatments with letrozole+human menopausal gonadotropin (LE+hMG) for ovarian stimulation. Results: The pregnancy outcomes were not associated with the attempts of failed OI cycles previously. Specifically, the clinical pregnancy rate was 21.14% for PCOS patients without previous OI cycles, 21.95% for PCOS patients with 1-2 previous OI cycles and 23.64% for PCOS patients with 3 or more previous OI cycles (p=0.507). The corresponding live birth rate was 16.64%, 18.06% and 18.68%, respectively, of which the difference was not statistically significant (p=0.627). The cumulative rate per patient was 38.59% for clinical pregnancy and 31.03% for live birth, and approximately 98% of the pregnancies occurred in the first three cycles of IUI. Conclusion: PCOS women with different attempts of OI cycles had similar pregnancy outcomes after IUI, thus a history of repeated failures of OI treatments was not a predictive factor for the pregnancy outcomes in IUI cycles. Most pregnancies occurred in the first three cycles of IUI, so we strongly recommended 3 attempts of IUI for PCOS women before they switched to IVF/ICSI. Generally, IUI might be an assist for infertile women with PCOS before IVF/ICSI and might accelerate pregnancy for target women without invasive manipulations.